Biomicroscopy of vessels of bulbarian conjunctives in diagnostics of gestation complications associated with development of thrombofilia - K V Zhmerenetsky; I A Bloshchinskaya; S A Bloshchinskiy (IP Berlin A.V., 2018)
Microthrombogenesis in the microcirculation system underlies many types of obstetric pathology. Objective. To substantiate the diagnostic significance of changes in the main parameters of microcirculation in the development of gestational complications associated with the manifestation of thrombophilia. Subects and methods. The method of biomicroscopy of the vessels of the bulbar conjunctiva and the study of the main parameters of the hemostatic system in 68 pregnant women with the established diagnosis of placental insufficiency from 24 patients with placental insufficiency development in connection with thrombophilia and 87 pregnant women with high thrombogenic risk with an unfavorable pregnancy outcome in history. Results. Characteristic changes in the microcirculation have been established both at the clinical stage of placental insufficiency caused by thrombophilia and before clinical manifestations of placental insufficiency: disturbances of venous outflow; the aggregate state of the blood elements. Conclusions. The method of biomicroscopy of vessels of bulbar conjunctiva can be used as a screening one to diagnose signs of placental insufficiency associated with the development of thrombophilia for the subsequent appointment of anticoagulant therapy.